Strategy of the Samosir Regency KPU in Holding Candidate Debates in the 2020 Regent and Deputy Regent Elections - Manalu, Ucok Simon; Kusmanto, Heri; Situmorang, Tonny Pangihutan (PERSPEKTIF, 2025)
The researcher raised this Thesis because of the researcher's interest in the strategy carried out by the Samosir Regency KPU to hold a Candidate Debate in the 2020 Samosir Regent and Deputy Regent elections. The Candidate Debate is a stage of the campaign that is highly anticipated by the community to be able to assess the candidate for the leader before giving his choice at the time of voting. The ResearcherResearcher wants to know the strategy for holding candidate debates in the 2020 Samosir regional election. In addition, what are the obstacles for the Samosir Regency KPU in holding a candidate debate event in the 2020 Samosir Regional Election? This research method is qualitative descriptive by presenting the data found comprehensively through in-depth analysis. Meanwhile, data analysis techniques consist of data reduction, data presentation, and conclusions drawn. The research results show that the community has not optimally felt the strategy for implementing candidate debates in the 2020 Samosir regional election because the approach of selecting the venue for the implementation and determining the invitation limits public participation. Likewise, the broadcasting strategy of debate events is considered not to be optimal for disseminating the profile, vision, and Mission, as well as the work program of the Candidate Pairs to the Voters by providing comprehensive information to the Voters as one of the Voters' considerations in making their choices.